2018
DOI: 10.1098/rspb.2018.1722
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of serial dependence

Abstract: The world tends to be stable from moment to moment, leading to strong serial correlations in natural scenes. As similar stimuli usually require similar behavioural responses, it is highly likely that the brain has developed strategies to leverage these regularities. A good deal of recent psychophysical evidence is beginning to show that the brain is sensitive to serial correlations, causing strong drifts in observer responses towards previously seen stimuli. However, it is still not clear that this tendency le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
303
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(358 citation statements)
references
References 38 publications
32
303
6
Order By: Relevance
“…Our work differs in that we focus on the temporal predictability of sensory inputs from one moment to the next. Others have suggested that serial dependence effects in perception might reflect an advantageous sensory integration strategy employed by the brain to improve behavior (Cicchini et al, 2014(Cicchini et al, , 2017(Cicchini et al, , 2018Fischer and Whitney, 2014). Very few of these studies, however, have cast this notion in an explicit normative framework.…”
Section: Discussionmentioning
confidence: 99%
“…Our work differs in that we focus on the temporal predictability of sensory inputs from one moment to the next. Others have suggested that serial dependence effects in perception might reflect an advantageous sensory integration strategy employed by the brain to improve behavior (Cicchini et al, 2014(Cicchini et al, , 2017(Cicchini et al, , 2018Fischer and Whitney, 2014). Very few of these studies, however, have cast this notion in an explicit normative framework.…”
Section: Discussionmentioning
confidence: 99%
“…Serial dependence, some argue, reflects the world's tendency to be stable 2,14,23 . The reasoning is that because similar stimuli usually elicit similar behavior, the brain would incorporate mechanisms to exploit these patterns 23 .…”
Section: Color Serial Dependence Builds Up In the Course Of An Experimentioning
confidence: 99%
“…Serial dependence, some argue, reflects the world's tendency to be stable 2,14,23 . The reasoning is that because similar stimuli usually elicit similar behavior, the brain would incorporate mechanisms to exploit these patterns 23 . Along these lines, a recent study has shown that systematic biases in color working memory change in the course of an experimental session to adapt to stimulus statistics 27 , arguing that systematic biases seen in delayed-estimation of color reflect real-world statistics.…”
Section: Color Serial Dependence Builds Up In the Course Of An Experimentioning
confidence: 99%
See 2 more Smart Citations